The interplay of iron, oxidative stress, and α-synuclein in Parkinson’s disease progression - Yan Chen; Xixi Luo; Yukun Yin; Elizabeth Rosalind Thomas; Kezhi Liu; Wenjun Wang; Xiang Li (Molecular Medicine)
Abstract The irreversible degeneration of dopamine neurons induced by α-synuclein (α-syn) aggregation in the substantia nigra is the central pathological feature of Parkinson's disease (PD). Neuroimaging and pathological autopsy studies consistently confirm significant iron accumulation in the brain of PD patients, suggesting a critical role for iron in disease progression. Current research has established that iron overload induces ferroptosis in dopaminergic neurons, evidence indicates that the impact of iron on PD pathology extends beyond ferroptosis. Iron also plays a regulatory role in modulating α-syn, affecting its aggregation, spatial conformation, post-translational modifications, and mRNA stability. Iron-induced α-syn aggregation can contribute to dopaminergic neurodegeneration through additional mechanisms, potentially creating a feedback loop in which α-syn further enhances iron accumulation, thus perpetuating a vicious cycle of neurotoxicity. Given α-syn’s intrinsically disordered structure, targeting iron metabolism presents a promising therapeutic strategy for PD. Therefore, the development of iron chelators, alone or in combination with other therapeutic drugs, may offer a beneficial approach to alleviating PD symptoms and slowing disease progression.